NUMERICAL STUDY OF THE INITIAL PRESSURE AND DIAMETERS RATIO EFFECT ON THE JET EJECTOR PERFORMANCE - Dahkil, Sadoun Fahad; Gabbar, Tahseen Ali; Jaber, Dhamia Khalf (Basrah Journal for Engineering Sciences, 2014)
In this paper, computation fluid dynamics model (CFD) is used to simulate a turbulence flow fields along the jet ejector. A Steady-state 2-D compressible flow model utilities the standard k- turbulent model has been used. The performance of jet ejector is simulated by FLUENT 6.3 (code) and GAMBIT software, using finite-volume scheme to solve transport NAVIER STOKE equations. The objective of this study is to investigate the high- performance of jet ejector geometry (mass flow and head ratio) nozzle to throat diameter at eight cases (DN/DT) with different initial pressure. Research is performed to optimize jet performance by varying initial pressure and nozzle diameter ratios from (1/8) to (8/8). To increase understanding of the axial velocity distribution at an important regions along the ejector, three regions are chosen, at inlet (1,3), nozzle exit(2) and midpoint of throat(4), with an important different diameters ratio cases 1,2,3,5,7 and 8 respectivly. The comparison of these results is presented by the axial velocity magnitude, mass and head ratio of the ejector at the above cases. Results show that higher pressure ratio and mass ratio (high performance) occur when the nozzle to throat diameter ratio (DN/DT) was (5/8) and (1/8) respectively. Also mass ratio is decreased at all initial pressure when the diameter ratio increased.